Human Herpesvirus 1 Associated with Epizootics in Belo Horizonte, Minas Gerais, Brazil - Gabriela Fernanda Garcia-Oliveira; Mikaelly Frasson Biccas; Daniel Jacob; Marcelle Alves Oliveira; Ana Maria de Oliveira Paschoal; Pedro Augusto Alves; Cecília Barreto; Daniel Ambrósio da Rocha Vilela; Érika Procópio Tostes Teixeira; Thiago Lima Stehling; Thais Melo Mendes; Marlise Costa Silva; et al. (Viruses)
Human activity in sylvatic environments and resulting contact with wildlife, such as non-human primates (NHPs), can lead to pathogen spillover or spillback. Both NHPs and humans host a variety of herpesviruses. While these viruses typically cause asymptomatic infections in their natural hosts, they can lead to severe disease or even death when they move into novel hosts. In early 2024, deaths of Callithrix penicillata, the black-tufted marmoset, were reported in an urban park in Belo Horizonte, Minas Gerais, Brazil. The epizootic was investigated in collaboration with CETAS/IBAMA and the Zoonoses Department of Belo Horizonte. Nine marmoset carcasses and four sick marmosets were found in the park; the latter exhibited severe neurological symptoms and systemic illness before succumbing within 48 h. Carcasses were tested for rabies virus and were all negative, and necropsy findings revealed widespread organ damage. In addition, the samples were tested for yellow fever virus, with negative results. Finally, molecular testing, viral isolation, and phylogenetic analysis demonstrated human herpesvirus 1 (HHV-1) as the causative agent. The likely source of infection was human-to-marmoset transmission, facilitated by close interactions such as feeding and handling. This study highlights the risks of pathogen spillover between humans and nonhuman primates, emphasizing the need for enhanced surveillance and public awareness to mitigate future epizootics.